Design and Analysis of 8 Bit Parallel Prefix Comparators Using Constant Delay Logic. (2016) - George, Amy Mariam; Chandran, G. Jyothish
Abstract: Parallel Prefix Radix 2 8 bit Comparators using Constant Delay (CD) logic is presented in this paper. The constant delay logic pre discharges the output to zero logic and switches to a logic one through a critical path clocked PMOS transistor. CD logic operation is much faster than a dynamic logic circuit during its D-Q mode of operation. The comparator's architecture consists of two stages; where the first stage uses a pass transistor pre encoding circuitry for achieving low power consumption and the second stage employs a high performance dynamic-CD-static logic manner combination comparators. Design and simulation were carried out in Mentor Graphics ELDO Simulator using 180 nm technology.